Serial processing in reading aloud: evidence for dual-route models of reading. - Coltheart, Max; Rastle, Kathleen (Journal of Experimental Psychology. Human Perception & Performance, 1994)
The authors examined the regularity effect on reading aloud as a function of left-to-right phonemic position of irregularity in low-frequency exception words. Ss named 96 low-frequency exception words categorized into 5 conditions on the basis of the position (1st through 5th) of their 1st irregular grapheme-to-phoneme correspondence (GPC). Latencies and error rates for these words were compared with the rates for 96 matched GPC regular controls. Results showed that the cost of irregularity decreased monotonically over the 5 positions of irregularity. This result is offered as evidence for dual-route models of reading and against parallel distributed processing models of reading. Reprinted by permission of the publisher.